Investigating the Effects of Spatial Confinement on Multicellular Morphogenesis - Hadjiantoniou, Sebastian Vasilis (Université d'Ottawa / University of Ottawa, 2018)
It has long been established that the physical properties of the cell’s surrounding microenvironment has the ability to impose its influence on a range of cell processes. Morphology, differentiation, and proliferation have all been shown to be sensitive to the mechanical cues inherent within the extracellular matrix. Although significant advancements in microfabrication and cell mechanics have been made, questions regarding how physical interactions guide biological systems in three dimensions remain unanswered. By utilizing cocultured systems and microfabricated channeled topographies, we reveal that the three dimensional nature of the environment is capable of driving cell patterning. Contact guidance is the phenomenon by which cells will orient themselves along the geometric patterns of a substrate. Much of its research has focused on the nano/micro scale of two dimensional topographies, affecting alignment along grooves. We have revealed that contact guidance has the ability to impose far more complex cellular behaviour in three dimensional systems. Furthermore, by modulating the elements of confinement surrounding cells, we directed the balance of binding forces between cells and substrate leading to significantly different cell type dependent morphologies. By then altering the geometry of the topography, we revealed the ability to induce cell type separation in cocultured systems. These concepts led to the subsequent discovery that confinement induces three dimensional spheroidal growth of embryonic stem cells. These results reveal that the element of confinement not only influences patterning in three dimensions but guides the fundamental early stages processes essential to all life.
Keywords: Microfabrication; Confinement; Stem cells; Binding energies